Stock price reaction to an arrangement approval in restructuring proceedings: The case of Poland - Błażej Prusak; Marcin Potrykus (International Journal of Management and Economics, 2022)
The study aims to empirically analyze the reaction of stock prices to the information about the conclusion and acceptance of a debtor-creditor arrangement under restructuring proceedings of companies listed on the stock exchange in Poland. The following main research hypothesis was verified: public disclosure of information about an arrangement conclusion and acceptance in restructuring proceedings results in above-average rates of return due to investments in the stocks of these entities in the short term. Three events were assessed: the public disclosure of information about the conclusion of a debtor-creditor arrangement (Event 1), its approval by a court (Event 2), and the decision becoming final (Event 3). The research method applied was the event study. Event 1 and Event 3 leads to an above-average and statistically significant increase in stock prices on the day of the event. In contrast, no statistically significant above-average rates of return accompanied Event 2.
Keywords: G11; G14; 650; event analysis; market efficiency; price reaction; restructuring proceedings